Compressive Strength Analysis of Mortar Made from Volcanic Sand in Nagari Aia Angek Based on Magnetic Mineral Content - Sumanti, Syahputri; Hamdi, -; Akmam, -; Amir, Harman; Syafriani, -; Ratnawulan, - (PILLAR OF PHYSICS, 2024)
Compressive strength testing is carried out on mortar made from a mixture of sand, cement and water. Mortar is one of the construction materials in building structures that has the main function as a material for construction parts. The compressive strength test is useful for measuring and knowing the strength of objects against compressive forces. The method used in this research is rock magnetism to determine the abundance of magnetic minerals and compressive strength testing to determine the relationship of compressive strength results to the magnetic minera content of Nagari Aia Angek volcanic sand. Volcanic sand is measured using a Bartington Susceptibility Meter Type MS2B with 3 forms of mineral separation treatment, namely Magnetic Mineral Reduction (PMM) with a value of χlf  505,99 x10 m-83 /kg, χfd (%) 2.72%, Additional Magnetic Minerals (TMM) with a value of χlf 1026.72 x10 m-83 /kg, χfd (%) 2.14%, and No Treatment (TP) with a value of χlf 853.98 x10 m-83 /kg, χlf (%) 2.16. The results of testing the compressive strength of mortar using Compression Testing Mechine on 3 volcanic sand treatments were obtained (PMM) with a value of 169.14 kg/cm2, (TMM) with a value of 147.11 kg/cm2, and (TP) with a value of 141.81 kg/cm2. The magnetic properties of volcanic sand samples are antiferrimagnetic and have superparamagnetic mixed grains and coarse grains. There is a relationship between the compressive strength value of mortar and the concentration of magnetic minerals, the higher the compressive strength value, the higher the χfd (%) value obtained